Analisis Pengaruh Motivasi Kerja, Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Perangkat Desa Di Kecamatan Gondang Kabupaten Bojonegoro - Saputri, Olivia Nathasa Novy; Sudaryanti, Dwiyani; Amin, Muhammad Sirojuddin (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to analyze the effect of work motivation, work discipline and work environment on the performance of village officials in Gondang District, Bojonegoro Regency. The data source of this research is primary data obtained from the time of distributing questionnaires to Village Apparatus in Gondang District and with a sample size of 87 respondents using saturated sample technique. The data analysis method uses multiple linear regression analysis with classical assumption tests and hypothesis testing. The results showed: (1) work motivation simultaneously has a positive and significant effect on the performance of village officials in Gondang Subdistrict, (2) work discipline simultaneously has a positive and significant effect on the performance of Village Officials in Gondang Subdistrict, (3) the work environment partially has an insignificant effect on the performance of Village officials in Gondang Subdistrict. Keywords: Work Motivation, Work Discipline, Work Environment, Employee Performance.